Letter to Editor: a giant peritoneal loose body in the pelvic cavity - Ke Wu; Qiu-Ling Wang; Wei Ren; Wu-Bin Guo (World Journal of Surgical Oncology)
Abstract A response to the case report by Zhang et al. and supplement another case of giant peritoneal loose body discovered due to abdominal pain. A 68-year-old man was admitted to the hospital with abdominal pain. CT revealed an ovoid mass in the pelvis measuring approximately 11.5 × 8.6 × 7.4 cm. During laparotomy, yellowish-white mass was identified within the pelvis. Histological examination revealed that the mass was hyalinized fibrous connective tissue with focal calcification. We report an extremely rare and interesting case.